MELURUSKAN KISAH CINTA YUSUF-ZULAIKHA; Analisis Riwayat Israiliyat dalam Kitab Jâmi’ Al-Bayân Karya Imam Al-Thabari - Fairuz Zabadi; Abd. Basid (Program Studi Ilmu Al-Qur’an dan Tafsir, Fakultas Ushuluddin, Universitas Annuqayah (UA), 2023)
Abstract Israiliyat spread widely through books of interpretation, stories of the prophets, and not infrequently from the talks of a few missionaries. In the case of Yusuf-Zulaikha, Israel succeeded in making the majority of Muslims in various parts of the world almost (or even already) believe that Zulaikha was the name of the wife of the king of Egypt who later became the wife of Prophet Yusuf. It is proven to be believed by the occurrence of Yusuf and Zulaikha's name in the prayers of the wedding ceremony. This research aims to reveal two things: First, what is the history of Israiliyat in the book Jamî' al-Bayân 'an Ta'wîli Âyât al-Qurân that is related to the story of Yusuf-Zulaikha? And Second, what is the quality of the Israeli narratives? To achieve that purpose, the writer relies on two theories at once. First, the historical theory that functions as research material to find out the consistency or inconsistency of the history of Israel; Second, the theory of al-jarh wa al-ta'dîl which is useful to know the credibility of each narrator. The connection between one narrator and another narrator will also be thoroughly studied through this theory. By using the qualitative research method, this research will produce the conclusion that, the enlightenment that is a little surprising that the assumption that is almost believed by the majority of Muslims about Zulaikha as the wife of al-'Aziz who later became the wife of Prophet Yusuf is sourced from the history of Israiliyat has so many flaws that it is not can be accepted, let alone believed to be true. Keywords: Israiliyat, Al-Thabar, Jami’ Al-Bayan, Youssef Zalkha